2004
DOI: 10.2472/jsms.53.207
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Humidity on Fatigue Crack Propagation Properties in Spherical Graphite Cast Iron

Abstract: The fatigue crack propagation test was carried out in order to clarify the effect of humidity on the characteristics of fatigue crack propagation in spherical graphite cast iron. Spherical graphite cast iron (FCD450) was used as a specimen. Then, two kinds of heat treatments were conducted to the material. One was an austemper treatment (ADI), the other was a quenching and tempering treatment (QT). Moreover, as cast material was added, and with these three materials fatigue crack propagation test was carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Usami et al reported that phenomena similar to this were also observed in austempered spheroidal graphite cast iron, and that these were acceleration phenomena (for the crack propagation rate) similar to water embrittlement. 5) In addition to the results of the crack propagation test performed in this study, it is assumed that the effects (Fig. 8(c) and (d)) brought about by humidity seen in the high ¦K region for both the PDI and FPDI.55 samples be induced because the phenomenon similar to water embrittlement affected the pearlite phases contained within both sample materials.…”
Section: Moisture Air Effects On Fatigue Crack Propagation Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Usami et al reported that phenomena similar to this were also observed in austempered spheroidal graphite cast iron, and that these were acceleration phenomena (for the crack propagation rate) similar to water embrittlement. 5) In addition to the results of the crack propagation test performed in this study, it is assumed that the effects (Fig. 8(c) and (d)) brought about by humidity seen in the high ¦K region for both the PDI and FPDI.55 samples be induced because the phenomenon similar to water embrittlement affected the pearlite phases contained within both sample materials.…”
Section: Moisture Air Effects On Fatigue Crack Propagation Propertiesmentioning
confidence: 99%
“…They also reported that even austempered spheroidal graphite cast iron made up of bainitic ferrite is also subjected to a phenomenon similar to water embrittlement. 5) In our previous work, we have also reported that the result of the fatigue crack propagation test using a two-phase spheroidal graphite cast iron comprised ferrite and bainitic ferrite demonstrated that a two-phase treatment was found to be effective in improving the fatigue crack propagation properties. 6) The findings described above suggest that atmospheric moisture may affect the fatigue crack propagation property of pearlite-containing spheroidal graphite cast iron, and that the ferrite phase may provide superior fatigue crack propagation resistance and may be able to reduce the effects of water embrittlement on pearlite matrices in spheroidal graphite cast iron containing both ferrite and pearlite.…”
Section: Introductionmentioning
confidence: 99%